Patient Involvement in Decisions regarding Emergency Department Discharge: A Multimethod Study - Marie Louise Thise Rasmussen; Kirsten Lomborg; Kasper Karmark Iversen; Hanne Konradsen (Emergency Medicine International)
Background. Unmet care needs and more than one reasonable discharge solution have been identified among patients in the emergency department. Less than half of the patients attending emergency care have reported being involved in decisions to the degree they have wanted. Having a person-centered approach, such as involving patients in decisions regarding their discharge, has been reported as being associated with beneficial outcomes for the patient. Aim. The aim of the study was to explore the extent of patients’ involvement in discharge planning in acute care and how patient involvement in decisions regarding discharge planning is managed in clinical practice. Methods. A multimethod study, including both quantitative and qualitative data, was carried out. The quantitative part included a descriptive and comparative analysis of additional data from the patient’s medical records and patient’s responses to the CollaboRATE questionnaire. The qualitative part included a content analysis of notes from field studies of interactions between healthcare professionals and patients. Results. A total of 615 patients from an emergency department at a medium-sized hospital completed the questionnaire. Roughly, a third gave top-box scores (36%), indicating optimal involvement in decisions. Two factors, being discharged home and not readmitted, were significantly associated with the experience of being involved. In clinical practice, there was a focus on symptoms, and diagnostic tools and choice of treatment were decisive for the further care trajectory of the patients. Speed and low continuity left limited opportunities for dialogue to uncover patients’ preferences. At the same time, the patients did not expect to be involved. Conclusions. Two out of three patients did not experience being involved in decisions regarding emergency department discharge. The interactions reflected an organizational structure in which the conditions for patient involvement were limited. Uncovering opportunities and initiatives to increase the number of patients who experience being involved in decisions is important tasks for the future.